To the question of the Russian–Czech–Slovak–Bulgarian–English paremiological core - Kotova, Marina Yu. (Bohemistyka, 2019)
Based on the Russian paremiological minimum of G. L. Permyakov and its reflection in the three Slavonic languages and the English language, determined by the methodology of one sociolinguistic paremiological experiment conducted in 2000-s by the author, this study is a further development of the G. L. Permyakov’s idea of the general international paremiological core. There is here the first representation of the Russian–Czech–Slovak–Bulgarian–English paremiological core as a condensation of a few author’s published collections of frequent current Slavonic and English proverbs, verified recently with the data of Internet space. Special attention is paid in this article to the characteristics of the Czech part of the analyzed paremiological core.